Nanocomposites of Layered Clays and graphene/graphene oxide for drug delivery - Hegazy, Nada Mahmoud (AUC Knowledge Fountain, 2015)
Layered double hydroxides (LDH) comprise a class of materials that can be either found as natural minerals or can be synthetically prepared. Their structure is composed of a mixture of divalent and trivalent metal cations, forming brucite-like layers, that are neutralized with anions in the interlayer gallery. They have unique physical and chemical characteristics such as: high surface area, large charge density, biocompatibility and exchange capacity. These have attracted attention to the LDHs as potential drug delivery vehicles. Graphene (G) has also attracted the attention to exceptional properties, such as huge surface area, charge density concentration, membrane permeability by piercing mechanism and many others, expanding its use to include biomedical applications, such as drug delivery. Moreover, the possibility of large scale production of exfoliated graphene oxide (GO) sheets from G offered a further opportunity for their use. GO has a high exposed oxygenated surface that allows loading of large number of drugs by different bonding interactions and is dispersible in water. Alendronate sodium is a water soluble nitrogen containing bisphosphonate (nBP) drug, that has low bioavailabilty (< 1 %) due to its low epithelial permeability. It also exhibits gastrointestinal adverse effects. The objective of the work is to create a hybrid nanocomposite of Zn-Al LDH in its nitrate form with G/GO, (G/GO-Zn-Al-NO3 LDH), combining the properties of these structures: membrane permeability and large interacting surface of G or GO, the buffering effect and the capability of the LDH in storing and controlling the drug release. The hybrid nanocomposites incorporated 2% w/w of G or GO with two different M2+/M3+ ratios of LDH, 2:1 and 3:1. They were loaded with the drug by co-precipitation and ion exchange. The samples were characterized by XRD, FTIR, Zetasizer analyzer, and the amount of drug loaded and released were determined by UV/Vis spectroscopy, and the results were compared to those of drug-LDH controls. Samples that have show successful intercalation of the drug in bi-layered arrangement are: co-precipitation samples using M2+/M3+ ratio of 3:1 (drug-LDH, G/GO-LDH), and ion-exchange samples, that don’t incorporate G/GO (drug-LDH), prepared using either M2+/M3+ ratios of 2:1or 3:1. Their loading amounts ranged from 25.4 to 51 % w/w, and they exhibited a sustained release over 24 hours with a release percentages, ranging from 2.1% (1.07 mg) up to 4.2 % (1.52 mg). The other samples showed loading by surface adsorption on brucite-like layers of the LDH and the G or GO. They have drug loading amounts ranging, from 12.4 to 57.3 % w/w. This work demonstrated the potential of G/GO-Zn-Al LDH nanocomposites for sustained drug delivery.